KMS Digital: Sistem Monitoring Tumbuh Kembang Balita Di Desa Lebakwangi - Satria Mandala; Adiwijaya; Endro Ariyanto; Eko Darwiyanto (CV. Multi Kreasi Media, 2025)
This community service program aims to develop a monitoring system for toddler growth and development through Digital KMS in Lebakwangi Village, Arjasari District, Bandung Regency, by integrating digital technology, improving digital literacy, encouraging active community participation, and utilizing local potential. This program is designed as a response to the limitations of the manual recording system that has been used so far, which often causes data input errors, delays in monitoring, and difficulties in early detection of growth disorders and nutritional problems in toddlers. Through an integrated approach, the activity began with the development of a Digital KMS system that included in-depth needs analysis with all stakeholders—from posyandu cadres and health workers to parents—to identify the constraints of traditional recording and determine the main features that must be included, such as automatic data input, notifications, and an interactive forum dashboard that displays data in real time. The stages of system development include needs analysis, user-friendly interface design, development of reporting and analytics modules, pilot testing in several strategic posyandu, and full implementation integrated with the local health system. This digital KMS application was built using Laravel tools for the backend and React for the frontend. Furthermore, the program improves digital literacy through workshops and technical training held at health centers and facilities, the creation of educational modules in the form of video tutorials, written guides, and interactive materials, as well as ongoing assistance with the formation of a technical support team that is ready to provide assistance in the field. A participatory approach is implemented through community discussion forums and the involvement of community leaders as agents of change to optimize system usage, enhance a sense of ownership, and empower the community to actively participate in system evaluation and improvement. In addition, data-based monitoring and evaluation are carried out by activating interactive dashboards for periodic monitoring, data collection and analysis for early risk identification, and periodic evaluation through surveys and questionnaires to compile evaluation reports as a basis for system improvement. Synergy among partners, involving local governments, educational institutions such as Telkom University, and local communities, strengthens the ecosystem supporting this program through strategic collaboration that ensures policy support, material development, and ongoing assistance. By utilizing existing geographical and infrastructure potential as well as the cultural value of mutual cooperation, this program has successfully implemented and socialized a digital KMS application that is expected to not only improve the accuracy and effectiveness of health monitoring for toddlers, but also empower the community through increased digital literacy and sustainable digital transformation, thereby generating a long-term positive impact on the quality of health services and the quality of life of children in Lebakwangi Village.